2018
DOI: 10.3892/ol.2018.7944
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of MYC binding protein promotes invasion and migration in gastric cancer

Abstract: Abstract. Gastric cancer (GC) is the second leading cause of cancer-associated mortality worldwide. Although the mortality rate of patients with GC has improved, it remains a significant health issue. The MYC proto-oncogene protein serves key roles in cellular proliferation, differentiation, transformation and apoptosis. Previous studies have identified the abnormal expression of MYC-binding protein (MYCBP) during tumorigenesis in multiple types of cancer. Furthermore, evidence demonstrates that the abnormal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…In order to verify the correlation between EYA4 and MYCBP, MYCBP was reported as a direct target of the β-catenin/LEF-1 pathway. 15,22 EYA4 was shown to mediate the Wnt pathway by dephosphorylating β-catenin Ser675 in pancreatic cancer. 15,23 Therefore, we hypothesized that EYA4 may mediate MYCBP by dephosphorylating β-catenin.…”
Section: Discussionmentioning
confidence: 99%
“…In order to verify the correlation between EYA4 and MYCBP, MYCBP was reported as a direct target of the β-catenin/LEF-1 pathway. 15,22 EYA4 was shown to mediate the Wnt pathway by dephosphorylating β-catenin Ser675 in pancreatic cancer. 15,23 Therefore, we hypothesized that EYA4 may mediate MYCBP by dephosphorylating β-catenin.…”
Section: Discussionmentioning
confidence: 99%
“…In esophageal cancer, miR-26a and miR-26b inhibit tumor cell proliferation by inhibition of MYCBP expression (22). Overexpression of MYCBP binding protein was found to promote the invasion and migration of gastric cancer (23). These findings indicate that MYCBP plays a carcinogenic role in most cancers.…”
Section: Introductionmentioning
confidence: 87%
“…Previous studies have suggested that MYCBP is an important regulator affecting the progression and development of tumors; for example, in glioma cells, the MYCBP mRNA expression increased along with the malignant grade (36). Moreover, in gastric cancer, Gong et al (37) reported that MYCBP mRNA expression was markedly increased compared with that in normal gastric tissues and knockdown of MYCBP inhibited the metastatic capacity. However, the influence of MYCBP on radiosensitivity is yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%